HUBUNGAN VISI DAN MISI SEKOLAH DENGAN PENINGKATAN MUTU KINERJA SEKOLAH - Sumantri, Agus; Gadriaman, Gadriaman; Jayusman, Iyus; Wibowo, Priyo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study was conducted in public junior high schools spread across West Java which are quality schools in the district/city, which amounted to 21 schools In this study the author used